Making the connection: social networks and type 2 diabetes among Black/African American Men: mixed-methods study protocol - Prochnow, Tyler; Smith, Matthew Lee; Patterson, Megan S.; Park, Jeong-Hui; Sherman, Ledric D. (Frontiers in Public Health, 2025)
This mixed-methods study protocol investigates the role of social networks in Type 2 diabetes (T2D) self-management among Black/African American (B/AA) men, a population disproportionately affected by T2D. The study employs a convergent design, combining quantitative social network analysis with longitudinal qualitative interviews. A nationally representative sample of 1,200 B/AA men with T2D will complete an online survey assessing their social networks, T2D self-management practices, and related psychosocial factors. A subset of 65 participants will engage in semi-structured interviews at two timepoints 6 months apart to explore the formation and evolution of supportive relationships. The study aims to: (1) identify specific aspects of social networks related to T2D self-management adherence, and (2) characterize the formation and evolution of relationships that improve T2D self-management strategies. Quantitative data will be analyzed using multivariate and multilevel regression techniques, while qualitative data will undergo thematic analysis. This comprehensive approach will provide insights into the structure and function of social networks among B/AA men with T2D, potentially informing culturally tailored interventions to improve T2D outcomes in this underserved population. The study’s innovative focus on the broader social context of T2D management among B/AA men has the potential to address health disparities and contribute to more effective strategies for reducing the burden of T2D in this population.